2011
DOI: 10.1159/000324988
|View full text |Cite
|
Sign up to set email alerts
|

Drusen Characteristics Revealed by Spectral-Domain Optical Coherence Tomography and Their Corresponding Fundus Autofluorescence Appearance in Dry Age-Related Macular Degeneration

Abstract: Purpose: To analyze the relationship between drusen morphology revealed by spectral-domain optical coherence tomography (SD-OCT) and corresponding fundus autofluorescence (FAF) features of the same drusen using the Heidelberg Retina Angiograph 2 (HRA2), in patients with dry age-related macular degeneration (AMD). Methods: Dry AMD patients were imaged with SD-OCT and HRA2 on the same day. SD-OCT B scans were then precisely overlaid onto the HRA2 images, and the SD-OCT morphological characteristics of the drusen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
0
24
1
Order By: Relevance
“…A hyper-reflective signal on cSLO IR reflectance has been previously described by our group for conventional drusen with RPE alterations 26. In a study of autofluorescence imaging in large drusen, Landa et al 27 suggested that hypoautofluorescent and hyperautofluorescent changes mostly correlate with the disruption of the overlying IS/OS layer. Current data from AO support the idea that different degrees of impairment in the RPE and photoreceptors could be responsible for the different imaging features recorded between medium–large drusen and reticular pseudodrusen.…”
Section: Discussionmentioning
confidence: 65%
“…A hyper-reflective signal on cSLO IR reflectance has been previously described by our group for conventional drusen with RPE alterations 26. In a study of autofluorescence imaging in large drusen, Landa et al 27 suggested that hypoautofluorescent and hyperautofluorescent changes mostly correlate with the disruption of the overlying IS/OS layer. Current data from AO support the idea that different degrees of impairment in the RPE and photoreceptors could be responsible for the different imaging features recorded between medium–large drusen and reticular pseudodrusen.…”
Section: Discussionmentioning
confidence: 65%
“…The measurements were performed subfoveally as well as 3,000 μm temporally and nasally of the fovea in the central horizontal OCT axis. Additionally, the frequencies of drusen, reticular drusen and RPE migrations, as well as presence and frequency of breaks of the ellipsoid portion of the inner segments of the photoreceptors (ISe) ≥ 50 μm were assessed [34,35] . Through the high-resolution OCT scans, a precise differentiation of the drusen ultrastructure with a qualitative discrimination via criteria established by Khanifar et al [29] could be accomplished.…”
Section: Morphological Examinationsmentioning
confidence: 99%
“…Several authors have specifically investigated SD-OCT characteristics at the site of visible drusen, including soft drusen by CFP [14,15,[17][18][19][27][28][29]. Khanifar et al demonstrated the existence of a wide variation in drusen morphology by SD-OCT, and differentiated 17 unique drusen patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Landa et al recently performed an SD-OCT/confocal scanning laser ophthalmoscope (cSLO) FAF correlation in patients with bilateral early AMD in areas of drusen primarily detected by SD-OCT [19]. They found that disruptions in the outer retina (i.e., the inner segment/ outer segment [IS/OS] layer) were closely related to local FAF changes.…”
Section: Introductionmentioning
confidence: 99%